Various Information Sources for HMM with Weighted Multiple Codebooks - Hacker, Christian; Stemmer, Georg; Steidl, Stefan; Nöth, Elmar; Niemann, Heinrich (Proceedings of the Speech Processing Workshop, Magdeburg, Germany, September 09, 2003)
When semicontinuous HMM are used for acoustic modeling in speech recognition usually all states share a single code book. In our investigations we split the feature set into independent subsets and use separate codebooks for each part. This provides a higher modeling flexibility while keeping the parameter space compact. Further experiments integrate new information sources by using additional codebooks which are estimated in a supervised training. For instance codebooks for phone transitions are applied. Codebook exponents weight the different information sources. Relative reductions in word error rate up to 20 % have been achieved.